Drug‐resistant parietal epilepsy: polymorphic ictal semiology does not preclude good post‐surgical outcome. Issue 1 (March 2015) - Francione, Stefano; Liava, Alexandra; Mai, Roberto; Nobili, Lino; Sartori, Ivana; Tassi, Laura; Scarpa, Pina; Cardinale, Francesco; Castana, Laura; Cossu, Massimo; Lo Russo, Giorgio
Abstract We investigated the anatomo‐electro‐clinical features and clinical outcome of surgical resections strictly confined to the parietal lobe in 40 consecutive patients who received surgery for pharmacoresistant seizures. The population was subcategorized into a paediatric (11 subjects; mean age at surgery: 7.2+/−3.7 years) and an adult group (29 patients; mean age at surgery: 30+/−10.8 years). The paediatric group more frequently exhibited personal antecedents, neurological impairment, high seizure frequency, and dysplastic lesions. Nonetheless, compared with adults, children had better outcome and more frequently reached definitive drug discontinuation after surgery. After a mean follow‐up of 9.4 years (range: 3.1–16.7), 30 subjects (75%) were classified as Engel Class I. The presence of multiple types of aura in the same patient, as well as a high incidence of secondary generalization, represented a characteristic feature of parietal seizures and did not correlate negatively with surgical outcome. A total resection of the epileptogenic zone and a localizing/regional interictal EEG were statistically significant predictive factors of outcome. Intracerebral investigation, performed in 55% of cases, contributed to complete tailored resections of the epileptogenic area and determination of prognosis. Frequent subjective manifestations of parietal lobe seizures, such as vertiginous, cephalic and visual‐moving sensations, underscore their potential misdiagnosis as non‐epileptic events.